(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Undernutrition is generally considered to be a major public health issue and is a principal cause of ill-health in many of the developing countries such as India. It increases the incidence of premature mortalities, morbidities and causes long-lasting physiological effects among children. Aims and objectives: The present cross-sectional study determines the prevalence of thinness [low Body Mass Index (BMI)-for-age] among pre-school children. It also studies the effects of certain socio-economic, socio-demographic and lifestyle variables on thinness. Subjects and Methods: The study was conducted among 1163 children (boys: 546; girls: 617) aged 2-5 years. All the children were covered by the Integrated Child Developed Scheme (ICDS) of the Government of India and were the beneficiaries of 24 ICDS centers located in Matigara block of Darjeeling district, West Bengal, India. Data was collected by visiting both the ICDS centers and the households of the children. Height and weight of the children were measured and BMI (weight/height2, kg/m2) was calculated. The new international BMI-based cut-off points of Cole et al. (2007) were utilized to determine the prevalence of thinness. Parents of the children were interviewed for data on socio-economic, sociodemographic and lifestyle variables. The data was statistically analyzed using SPSS (Version 17.0). The statistical tests performed were chi-square analysis, ANOVA and multinomial logistic regression. Results: The overall mean BMI among the boys and girls were 14.42 ±1.73 kg/m. and 13.91 ±1.64 kg/m., respectively (p<0.05). The sex-specific prevalence of thinness was significantly greater among girls (67.91%) than boys (55.12%) (p<0.05). The age-specific overall thinness was observed to be the greater in case of boys and girls aged 5 years (57.95% and 71.49%). Results of the multinomial logistic regression analysis showed that sex, age, study area, father’s occupation and toilet facility exhibited significant effects on the grades of thinness (p<0.05). Conclusion: Very high prevalence of thinness was present among the pre-school children and this was indicative of major nutritional deprivation. Appropriate nutritional intervention and proper monitoring of the ongoing intervention programmes are necessary to ameliorate their existing nutritional status among children.